Novel Mutation in CACNA1A Associated with Activity-Induced Dystonia, Cervical Dystonia, and Mild Ataxia. (3rd August 2021) - Stampfl, Benjamin; Fee, Dominic
Abstract : CACNA1A encodes the pore-forming α 1 subunit of the neuronal voltage-gated Cav2.1 (P/Q-type) channels, which are predominantly localized at the presynaptic terminals of the brain and cerebellar neurons and play an important role in controlling neurotransmitter release. Mutations in CACNA1A have been associated with several autosomal dominant neurologic disorders, including familial hemiplegic migraine type 1, episodic ataxia type 2 (EA2), and spinocerebellar ataxia type 6. A 37-year-old woman presented with a history of slowly progressive, activity-induced stiffness, and pain in her right leg since age 15 and cervical dystonia since age 20. She denied any right leg stiffness or pain at rest, but when she began to walk, her right foot turned in and her right leg stiffened up. She also had neck pain, stiffness, and spams. There was no family history of similar symptoms. On physical exam, her strength, tone, and reflexes were normal in all extremities at rest. There was mild head titubation and very mild past pointing on finger-to-nose testing. MRI of the brain and spinal cord was unremarkable. This patient's clinical picture was felt to be most consistent with paroxysmal kinesigenic dyskinesia, as she has attacks of dystonia that are triggered by voluntary movement, last from a few seconds to a minute, and are relieved with rest. She was trialed on carbidopa/levodopa without improvement. A dystonia panel showed two potentially pathologic mutations, one in CACNA1A and the other in PNKP, along with a variant of unknown significance in ATP7B . The mutation in CACNA1A is C2324 G < A. It is heterozygous, autosomal dominant, and computer modeling suggests pathogenicity. This mutation has not been reported previously and is likely the cause of her paroxysmal dystonia; dystonia is sometimes seen during episodes of ataxia in EA2, and CACNA1A knockout mice exhibit dystonia and cerebellar atrophy. After receiving her genetic diagnosis, the patient was trialed on acetazolamide without improvement in her dystonia symptoms. This is the second case report of a patient with cervical dystonia and cerebellar ataxia associated with a mutation in CACNA1A .